Integrating Total Physical Respond with Help Flashcards to Teach English Vocabulary to Young Learner - Feti Dwijayanti; Kristi Nuraini (JELP Journal of English Language and Pedagogy, 2025)
This study investigates the integration of Total Physical Response (TPR) and flashcards as a combined media to enhance vocabulary acquisition. TPR links words with physical actions, engaging multiple senses, while flashcards provide visual reinforcement and repeated exposure. A review of 15 studies reveals that combining TPR and flashcards significantly improves vocabulary retention, comprehension, and engagement. TPR's kinaesthetic activities support long-term memory, particularly for kinaesthetic learners, while flashcards offer visual cues and interactive features that benefit diverse learners. Digital flashcards, like those on Quizlet, add gamification and promote autonomous learning, boosting motivation. This multimodal approach creates an inclusive, stress-free learning environment suitable even for students with dyslexia or visual impairments. However, challenges such as the need for teacher training, limited resources, and difficulty applying TPR to abstract vocabulary were noted. Recommendations include professional development, structured lesson plans, and using both traditional and digital tools to optimize outcomes. This integrative method offers promising potential for improving English vocabulary instruction for young learners